MODERNIZATION THERAPY OF PATIENTS WITH GASTROINTESTINAL DISEASE BY USING MAGNESIUM-MINERAL COMPLEX - Хайменова, Г.С.; Янчук, О.А. (World of Medicine and Biology, 2015)
Non-alcoholic fatty liver disease (NAFLD) – it is a diffuse polietiological dismetabolic process lasts more than 6 months and includes fatty degeneration of hepatocytes with gistolymphocytic infiltration of the liver lobules, per sinusoidal stellate cells hyperplasia and fibrosis of the liver with preservation of architectonic (EM Brunt, 2004). Our main goal was to investigate the efficacy and tolerability Detoksmag («DETOXMAG") in the treatment of patients with non-alcoholic fatty liver disease. The data obtained concluded that use of the drug Detoksmag («DETOXMAG") on the basis of Bishofit Poltava field in the treatment of NAFLD with elevated lipid profile leads to improved well-being of patients, normalization of biochemical parameters, lipid profile normalized, preventing the progression of the disease, all of which improves the quality of life of patients.
Keywords: non-alcoholic fatty liver disease; pathogenetic therapy; Bischofit Poltava deposit; magnesium-mineral complex